PENDISTRIBUSIAN PRODUK YANG OPTIMAL DENGAN METODE TRANSPORTASI - Rosta, Jevi; Tannady, Hendy (Teknik dan Ilmu Komputer, 2012)
Distance and capacity are the main obstacles to save the costs incurred by the distributions of products in manufacturing industry, which sometimes causea major loss for a company. This research focuseson minimizing the costs resulting from the distribution from the factory to the warehouse, the capacity incompatibility between the factory and warehouse in using the transportation method. The study objective is to find the most optimum capacity and thetransportation costs.Â Keywords: distance, capacity, optimum, transportation methods